(3TQM aUhd CHbQGWs - (3CHh GdbGSe YHO GdQMef Hf Ydj Hf CHi UGObs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3CeG HYO MeO Gddg HLejY eMGeOg , hGdUdGI Ydi QShdg eMeO GdfHi hBdg hSde hbO cGf ef GdeJbOejf hGdeJCNQjf eef JcdehG ai GdWH QChG Cf jOhfhG HYOge LedG hLhGeY ef GUhdg s
(3BNQgG (B:s
(3hCeG GdaUhd GdeOdSI hGdJi bO CYjO PcQgG HCNQI ef GdcJGH , abO JQcfG PcQgG TabI Ydi ahJ GdReGf HeGdG jLOi faYkG , hGddg JYGdi hdi GdNjQ hGdNjQI s
(3fSNI SGOSIs
(3hGdChQGb GdKdGKI GdCNjQI efgG Hbde eZGjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdWH (B- (3U (B110 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B131 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B250 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(877) s
Keywords: (3GdWHs